Approximate Solution of Urysohn Integral Equations Using the Adomian Decomposition Method - Randhir Singh; Gnaneshwar Nelakanti; Jitendra Kumar (The Scientific World Journal)
We apply Adomian decomposition method (ADM) for obtaining approximate series solution of Urysohn integral equations. The ADM provides a direct recursive scheme for solving such problems approximately. The approximations of the solution are obtained in the form of series with easily calculable components. Furthermore, we also discuss the convergence and error analysis of the ADM. Moreover, three numerical examples are included to demonstrate the accuracy and applicability of the method.